Production of biomaterials from cork: Liquefaction in polyhydric alcohols at moderate temperatures - Yona, Arnaud Maxime Cheumani; Budija, Franc; Kričej, Borut; Kutnar, Andreja; Pavlič, Matjaž; Pori, Pavel; Tavzes, Črtomir; Petrič, Marko (Industrial Crops and Products, 2014)
The aim of this study was to develop polymers in a liquid solution, from renewable bio-resources, usable as intermediate materials in the preparation of plastics, adhesives or coatings. The liquefaction of cork with glycerol was investigated at 150◦C, 180◦C, and 200◦C under acidic (sulphuric acid) or alkaline conditions (sodium hydroxide). Cork appears as a two-component material, containing suberin and lig- nocelluloses. In the presence of sulphuric acid, only the liquefaction of the lignocellulosic components was achieved, leading to liquefaction yield of less than 47% at all investigated conditions. The inverse phenomenon was observed with sodium hydroxide. Suberin was almost completely liquefied, but an increase of temperature and/or sodium hydroxide content was necessary to improve the liquefaction of lignocelluloses. Addition of polyethylene glycol to glycerol to a certain extent caused the conversion of suberin under acid conditions leading to liquefaction yield up to 93%. Therefore, it was demonstrated that it is possible to use cork dust, a less valuable by-product, for the production of various basic chemicals and/or polymers with a high added value
Keywords: Cork; Glycerol; Liquefaction; Polyethylene glycol; suberin